2017
DOI: 10.1038/s41598-017-05803-1
|View full text |Cite
|
Sign up to set email alerts
|

Intended outcome expands in time

Abstract: Intentional agents desire specific outcomes and perform actions to obtain those outcomes. However, whether getting such desired (intended) outcomes change our subjective experience of the duration of that outcome is unknown. Using a temporal bisection task, we investigated the changes in temporal perception of the outcome as a function of whether it was intended or not. Before each trial, participants intended to see one of two possible outcomes but received the intended outcome only in half of the trials. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 78 publications
2
18
0
Order By: Relevance
“…A simple test of this hypothesis would be to measure the subjective duration of the outcome; more attention would result in a longer perceived outcome durations in causal, compared to non-causal trials. Related to this idea Makwana and Srinivasan (2017) reported that outcomes that were intended by the participants appeared to last subjectively longer than unintended outcomes. Empirically, a systematic drift in attention could also explain the results of Experiments 3 and 4, because fewer clock pulses, overall, would accumulate during causal, than non-causal intervals.…”
Section: Where Is Attention Allocated In Temporal Binding?mentioning
confidence: 99%
“…A simple test of this hypothesis would be to measure the subjective duration of the outcome; more attention would result in a longer perceived outcome durations in causal, compared to non-causal trials. Related to this idea Makwana and Srinivasan (2017) reported that outcomes that were intended by the participants appeared to last subjectively longer than unintended outcomes. Empirically, a systematic drift in attention could also explain the results of Experiments 3 and 4, because fewer clock pulses, overall, would accumulate during causal, than non-causal intervals.…”
Section: Where Is Attention Allocated In Temporal Binding?mentioning
confidence: 99%
“…This suggests a possibility that onset timing, but not offset timing, shifts perception toward the action, and as a result, the event duration is expanded. A recent study (Makwana & Srinivasan, 2017) If this model is true, where the perceptual duration of the event dilates, we can further speculate that the perception of onset should be difficult or imprecise, since the actual timing to be judged presents itself without a clear perceptual edge (i.e., for a subjectively expanded event). Indeed, the data from Experiment 3 supports this, the variance of reported timing of the tone was significantly larger than baseline, regardless of agency conditions ( Figure S5), suggesting that the time perception was less precise in action-outcome situations, especially for tone.…”
Section: Only "Onset" Shifts (Model 2)mentioning
confidence: 74%
“…The key purpose of the current study was to temporally examine onset and offset agency. The former can be defined as the subjective feeling of generating an action itself, as well as through a difference in time perception (delay detection, duration estimation, or timing report) (Engbert et al, 2007;Haggard et al, 2002;Makwana & Srinivasan, 2017) c.f. (Farrer et al, 2013) in the sensory event generated by the action.…”
Section: Onset/offset Agencymentioning
confidence: 99%
“…However, it is still unclear whether an action irrelevant to the stimulus-motion speed changes the apparent-motion speed; if it does, there would be two possible explanations: either an action affects the apparent-motion speed directly or it affects the apparent-motion speed indirectly via the change in the apparent duration of the motion stimulus because the duration of stimuli following an action (e.g. saccade) was known to appear to be longer in consequent stimuli (chronostasis) [13, 14], resulting in that the estimation of speed will decrease if the motion system calculates the speed as spatial displacement per an unit time. Because speed changes proportionally with duration when the movement distance is physically fixed, the change in apparent speed of a moving stimulus should covary with the apparent duration of that stimulus.…”
Section: Introductionmentioning
confidence: 99%